A novel microsurgical rodent model for the transplantation of engineered cardiac muscle flap. Issue 5 (6th April 2018) - Tee, Richard; Morrison, Wayne Allan; Dilley, Rodney J.
Abstract : Background: The survival of engineered cardiac muscle 'grafts' to the epicardium is limited by vascularization post‐transplantation in rat models. In this article, we describe the methodology of a novel rat model that allows for the transplantation of an engineered cardiac muscle flap (ECMF) onto the epicardium. Materials and Methods: A total of 40 rats were used. Twenty‐four neonatal rats were used to harvest cardiomyocytes. At week 1, ECMF were generated by seeding cardiomyocytes into the arteriovenous loop (AVL) tissue engineering chamber implanted into the right groin of adult rats (n = 8). At week 6, the ECMF were harvested based on a pedicle along the femoral‐iliac‐abdominal vessel and anastomosed to the neck vessels of the recipient syngeneic adult rats (n = 8). The flaps were delivered into the thoracic cavity and onto the epicardium. The transplanted flaps were harvested at week 10. Survival of the flaps was assessed by the patency of anastomoses and viability of the cardiomyocytes through histological analysis (hematoxylin and eosin [H&E], desmin, and von Willebrand factor [vWF] immunostaining). Results: Six out of 8 rats survived the transplantation procedure. These remaining 6 recipient rats survived until harvest time point at 4 weeks post‐transplantation. The mean area of the flap was 46.7mm 2 . Six out of 6 flaps harvested at week 10 showed viable cardiomyocytes using desmin immunostaining and vascular channels were seen at the interface between flap and epicardium. Conclusion: This is a technically feasible model that will be useful for future assessment of different cardiac stem cell implants and their functional significance in rat heart models.